Comparative genomics of Fructobacillus spp. and Leuconostoc spp. reveals niche-specific evolution of Fructobacillus spp. - Akihito Endo; Yasuhiro Tanizawa; Naoto Tanaka; Shintaro Maeno; Himanshu Kumar; Yuh Shiwa; Sanae Okada; Hirofumi Yoshikawa; Leon Dicks; Junichi Nakagawa; Masanori Arita (BIOMED CENTRAL LTD, 2022)
Background: Fructobacillus spp. in fructose-rich niches belong to the family Leuconostocaceae. They were originally classified as Leuconostoc spp., but were later grouped into a novel genus, Fructobacillus, based on their phylogenetic position, morphology and specific biochemical characteristics. The unique characters, so called fructophilic characteristics, had not been reported in the group of lactic acid bacteria, suggesting unique evolution at the genome level. Here we studied four draft genome sequences of Fructobacillus spp. and compared their metabolic properties against those of Leuconostoc spp.Results: Fructobacillus species possess significantly less protein coding sequences in their small genomes. The number of genes was significantly smaller in carbohydrate transport and metabolism. Several other metabolic pathways, including TCA cycle, ubiquinone and other terpenoid-quinone biosynthesis and phosphotransferase systems, were characterized as discriminative pathways between the two genera. The adhE gene for bifunctional acetaldehyde/alcohol dehydrogenase, and genes for subunits of the pyruvate dehydrogenase complex were absent in Fructobacillus spp. The two genera also show different levels of GC contents, which are mainly due to the different GC contents at the third codon position.Conclusion: The present genome characteristics in Fructobacillus spp. suggest reductive evolution that took place to adapt to specific niches.